Management of anophthalmia, microphthalmia and coloboma in the newborn, shared care between neonatologist and ophthalmologist: a literature review - Monica Russo; Serena Palmeri; Alice Zucconi; Aldo Vagge; Cesare Arioni (Italian Journal of Pediatrics)
Abstract Congenital ocular anomalies significantly contribute to global disability, with 15–20% of infant blindness attributed to these anomalies. This study examined anophthalmia, microphthalmia, and coloboma (AMC) through collaborative neonatology and ophthalmology care. The global prevalence of AMC varies: anophthalmia at 0.6–4.2 per 100,000 births and microphthalmia at 2–17 per 100,000 births, with a combined prevalence of up to 30 per 100,000. The prevalence of coloboma, alone or associate with other eye defects is 2–19 per 100,000 live births. Anophthalmia and microphthalmia may present as isolated or genetic syndromes, necessitating comprehensive evaluation. AMC etiology encompasses genetic and environmental factors. Chromosomal aberrations and mutations in genes such as PAX6, SOX2, OTX2, and CHD7 are contributors. Syndromic associations, such as CHARGE (heart defect, atresia choanae, retarded growth and development, genital hypoplasia, ear anomalies/deafness) syndrome, underscore the complexity of this syndrome. Early AMC diagnosis is pivotal for timely intervention. This work provides a literature review offering insights for effective management and genetic counseling in a pediatric context.